Potential Conflict between the Malay and the Dayak Ethnic Groups in the Hinterland Region of West Kalimantan - Alfath, Edlin Dahnia (UI Scholars Hub, 2015)
This research was conducted in two villages in the hinterland region of West Kalimantan. The two villages are separated only by a small stream, and they are inhabited by two different ethnic groups. Seen from the upstream of the river, the left side of the riverbank is where the Dayak lived, while at the right side of the riverbank is where the Malay ethnic resided. The Malay, as Muslims, led their live according to Islamic teaching, while the Dayak is oblivious to their neighbor’s Islamic way of life. This in turn had fostered seeds of tensions with a potential for a conflict in the social relation between the two groups. Fortunately, the potential for conflict has not erupted into an open confrontation between them. The objective of this study is to find out the background issues that breed the potency of conflict between these two ethnic groups, the Malay and the Dayak, and why it never erupted into an open confrontation.